Susceptibility and carrier status of impala, sable and tsessebe for Cowdria ruminantium infection (heartwater) - Peter, T.F.; Anderson, E.C.; Burridge, M.J.; Perry, Brian D.; Mahan, S.M. (1999)
Three species of wild African ruminants. impala (Aepyceros melampus), sable (Hippotragus equinus, and tsessebe (Damaliscus lunatus), were experimentally inoculated with in vitro culture-derived Cowdria ruminantium organisms, the tick-borne causative agent of heartwater in domestic ruminants, to determine their susceptibility to infection. No clinical disease was observed in any of the ruminants. However. C. ruminantium was detected in the sable by the transmission of heartwater to susceptible sheep through the tick vector Amblyomma hebraeum, at 10 and 37 days postinfection (PI). Attempts to detect infection in the impala and tsessebe by tick transmission at 54 days PI failed. The impala and tsessebe were reinoculated with C. ruminatum organisms at 146 days after the first inoculation: however. a tick transmission attempt at 66 days after the reinoculation also failed. Seroconversion as detected by immunoblotting was demonstrated in the sable and the tsessebe but not in the impala. The results demonstrate that sable can be carriers of C. ruminantium. The susceptibility of tsessebe and impala, however, remains undetermined.